2002
DOI: 10.1116/1.1531140
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ar and O2 additives on SiO2 etching in C4F8-based plasmas

Abstract: Gas mixtures based on C4F8 are promising for the development of high-performance SiO2 plasma etching processes. Measurements of important gas phase species, thin film etching rates and surface chemistry changes were performed for inductively coupled plasmas fed with C4F8/Ar and C4F8/O2 gas mixtures. The addition of Ar to C4F8 causes a strong increase of the plasma density relative to that of pure C4F8 (by up to a factor of 4× at 90% Ar). For O2 addition the changes in plasma density are small up to 90% O2 rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
56
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(64 citation statements)
references
References 14 publications
8
56
0
Order By: Relevance
“…The C (1s) peak profile for a specific set of plasma operating conditions was very reproducible regardless of the base substrate used (Au, Si, or HOPG) or the sample position in the plasma reactor during layer deposition. Similar results have been also reported in the literature for plasma deposition on Si substrates from a C 4 F 8 gas source but at different conditions [5][6][7] .…”
Section: S3supporting
confidence: 79%
“…The C (1s) peak profile for a specific set of plasma operating conditions was very reproducible regardless of the base substrate used (Au, Si, or HOPG) or the sample position in the plasma reactor during layer deposition. Similar results have been also reported in the literature for plasma deposition on Si substrates from a C 4 F 8 gas source but at different conditions [5][6][7] .…”
Section: S3supporting
confidence: 79%
“…In principle, the concentration of argon plays an important role for plasma etch mechanisms. Li et al showed that during etching of fused silica by the use of fluorine-based plasmas, an increase in argon concentration allows increasing the etch rate [15]. For pure silicon, Coburn and Winters observed certain etching by pure argon ion bombardment [16].…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers showed the electron temperature of Ar added C 4 F 8 plasma was higher than that in pure C 4 F 8 plasma. [10][11][12] They pointed out that this is because the ionization energy of C 4 F 8 ͑about 12 eV͒ is lower than that of Ar gas ͑about 15 eV͒. However, they also found that the SiO 2 etching rate in C 4 F 8 plasma decreased with Ar dilution because of the decrease in CF 3 ϩ ion density, even though the electron temperature was increased.…”
Section: B Mechanism Of High Sio 2 -Etching Rate and Etching Selectimentioning
confidence: 85%